KOMBINASI DEEP BREATHING DAN CHEST MOBILITY DALAM MENINGKATKAN KAPASITAS PARU PADA KASUS EFUSI PLEURA - Pahlawi, Riza; Zahra, Salma (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: the pleura effusion is a circumstance characterized by a buildup of fluid in the pleura cavities on the surface of pleura visceral and pleura pariental. Besides the fluid, the pleura effusion also contains pus and blood. Pleura sufferers commonly complain of shortness of breath, pain in the chest wall area, ineffective breathing patterns, posture disorders, a decline in chest expansion that would result in diminished lung capacity. Deep breathing is thought to reduce respiratory work and improve the efficiency of respiratory ventilation. Chest mobility are effective in improving chest mobility, improving respiratory ventilation, controlling inspiration and spiraling. Purpose: to identify the effects of deep breathing and chest excretion to increase lung capacity in the case of the pleura efusi. Method: a single case study conducted with physiotherapy interventions on patients with the diagnosis of a 52-year-old pleura of deep breathing and chest training during the 6 evaluation. The dyspnea assessment is measured with a dyspnea desired scale, a thorax expansion with a midline and a pulmonary capacity of inspiring volume with spirometry incentives. Results: the case study shows that there is a decrease in density, increased thoraks expansion and increased lung capacity at inspiration volume by 500 ml to 800 ml. Conclusion: the study showed that increased lung capacity was given deep breathing and chest mobility.